Basics of digital photography in dermatology - Miot, Hélio Amante [UNESP]; Paixão, Maurício Pedreira; Paschoal, Francisco Macedo (FapUNIFESP (SciELO), 2006)
Digital technology has promoted a great popularization of photographic registration in several medical areas. Because of its visual nature, dermatology has incorporated the benefits of this tool in clinical practice and research. This article aims to offer guidance to the dermatologist who is unfamiliar with this technology, providing basic understanding for the best use of digital photography equipment. ©2006 by Anais Brasileiros de Dermatologia.
Keywords: Dermatology; Methods; Photography; clinical practice; dermatology; digital imaging; photography; review; technology